Reciprocal regulation of chromatin state and architecture by HOTAIRM1 contributes to temporal collinear HOXA gene activation - Wang, Xue Q. D.; Dostie, Josée (Nucleic acids research, 2017)
Thousands of long non-coding RNAs (lncRNAs) have been identified in mammals, many of which represent important regulators of gene expression. However, the mechanisms used by lncRNAs to control transcription remain largely uncharacterized. Here, we report on HOTAIRM1, a promising lncRNA biomarker in leukemia and solid tumors. We find that HOTAIRM1 contributes to three-dimensional chromatin organization changes required for the temporal collinear activation of HOXA genes. We show that distinct HOTAIRM1 variants preferentially associate with either UTX/MLL or PRC2 complexes to modulate the levels of activating and silencing marks at the bivalent domain. HOTAIRM1 contributes to physical dissociation of chromatin loops at the cluster proximal end, which delays recruitment of the histone demethylase UTX and transcription of central HOXA genes. Interestingly, we find overall proximal HOXA gene activation without chromatin conformation changes by HOTAIRM1 in a different cell type. Our results reveal a previously unappreciated relationship between chromatin structure, architecture and lncRNA function.